Absorbable Barbed Continuous versus Nonabsorbable Nonbarbed Interrupted Suturing Methods for Donor-site Closure of the Rectus Abdominis Myocutaneous Flap. Issue 1 (12th January 2023) - Kitano, Daiki; Nomura, Tadashi; Sakakibara, Shunsuke; Terashi, Hiroto
Abstract : Background: Abdominal incisional hernia is a complication of the rectus abdominis myocutaneous (RAMC) flap harvest. This study aimed to compare the incidence of abdominal incisional hernia and donor-site closure time between absorbable barbed continuous (ABC) and non-absorbable non-barbed interrupted (nAnBI) methods. Methods: This study included 145 patients who underwent free RAMC flap reconstruction after head and neck cancer surgery at Kobe University Hospital between January 2012 and March 2020. The nAnBI method was selected between January 2012 and August 2016, and the ABC method was selected between September 2016 and March 2020. The incidence of abdominal incisional hernia and the average time required for donor-site closure were compared between the two groups. Results: Of the 145 patients surveyed, 116 (57 and 59 in the nAnBI and ABC groups, respectively) were followed-up for at least 90 days after the surgery. The incidence rates of abdominal incisional hernia were 0% and 5.1% (n = 3) in the nAnBI and ABC groups, respectively, with no significant differences ( p = 0.244). The average donor-site closure times were 127.6 and 111.3 minutes in the nAnBI and ABC groups, respectively, with no significant differences ( p = 0.122). Conclusions: No significant differences in the incidence of abdominal incisional hernia and donor-site closure time were observed between the nAnBI and ABC groups. However, there was a tendency for increased hernia occurrence and shorter wound closure time in the ABC group. A randomized prospective multicenter study is warranted to validate our findings of the ABC method.